The impact of headache specialist density and the introduction of gepants and lasmitidan on prescriptions for acute migraine treatments: a regression and interrupted time series analysis - Leon S. Moskatel; Rebecca Y. Linfield; Niushen Zhang (Frontiers in Neurology)
BackgroundUnderstanding all factors that affect a patient’s acute migraine treatment care is crucial. We sought to determine the impact of headache specialist density and the introduction of the gepants and lasmiditan on the prescription of acute treatments for migraine.MethodsWe analyzed three scenarios: first, we performed linear regression analysis with the percentage of patients with migraine prescribed an acute medication in 2023, obtained via Epic Cosmos, and the density of headache specialists at the state level. Second, we conducted interrupted time-series analysis examining the change in patients prescribed the triptans before (2016–2019) and after (2020–2023) the introduction of the gepants and lasmiditan. Finally, we used regression analysis to look at the association of one pharmaceutical company, Pfizer, payments to physicians with prescriptions for that company’s gepant, rimegepant.ResultsWe included 6,559,854 patients with migraine and found that increased headache specialist density was associated with increased eletriptan, almotriptan, and naratriptan; there was no association with the other queried acute medications. In our interrupted time-series analysis, the introduction of the gepants and lasmiditan was linked to decreases in triptan utilization, except for eletriptan which remained stable, and rizatriptan which rose at a slower rate. Finally, increased Pfizer payments to physicians were associated with a higher percentage of patients prescribed rimegepant.ConclusionOur study suggests increased headache provider availability is associated with more prescriptions for naratriptan, eletriptan, and almotriptan. Additionally, the introduction of the gepants and lasmiditan broadly decreased the utilization of triptans. Critically, there was a strong association between a pharmaceutical company’s, Pfizer, payments to physicians and utilization of their medication, rimegepant.